(untitled) - Purcell, Edward M. (New York, 1965)
The textbook covers all the standard introductory topics, such as electrostatics, magnetism, circuits, electromagnetic waves and electric and magnetic fields in matter. Taking a non-traditional approach, magnetism is derived as a relativistic effect. Mathematical concepts are introduced in parallel with the physics topics at hand, making the motivations clear.
Keywords: Electricity,Magnetism,Từ học,Điện học